The Effectiveness of Diversion in the Resolution of Cases Involving Children in Conflict with the Law (ABH): An Analysis of Implementation, Juridical Constraints, and the Impact on Restorative Justice - Roy Parlaungan Simamora; Triono Eddy (PT FORMOSA CENDEKIA GLOBAL, 2026)
Children in Conflict with the Law (ABH) require special protection in the criminal justice system. One form of such protection is Diversion, which is the resolution of children's cases outside of formal justice based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study aims to analyze the effectiveness of Diversion implementation, the obstacles encountered, and efforts to improve its implementation. The research method used is normative-empirical with a descriptive-analytical nature, through legislative, conceptual, case, and sociological-juridical approaches. Data were obtained from literature studies, interviews, and documentation, then analyzed qualitatively. The results of the study indicate that Diversion is quite effective in resolving minor cases of children because it is able to prevent children from the stigma of justice, restore the relationship between the perpetrator and the victim, and support the best interests of the child. However, its implementation still faces legal and sociological obstacles, such as regulatory restrictions, differences in understanding of the authorities, and lack of support from victims and families. Therefore, it is necessary to strengthen the capacity of the authorities and support the social environment so that Diversion runs more optimally.